Comparison of Flood Hydrograph of Manikin Dam Watershed Using Synthetic Unit Hydrograph Method, HEC-HMS and Rain on Grid Model with HEC-RAS 2D - Mariano Ado Galot Pukan; Umboro Lasminto (Journal of Civil Engineering, 2025)
Manikin watershed is located in Kuaklalo Village which borders Bokong Village, Taebenu Subdistrict, Kupang Regency, East Nusa Tenggara Province which has an area of 49.31 km2 with a river length of 8.62 km which has a semi-arid climate with a fairly high annual rainfall of around 1000 - 1500 mm. This study aims to compare the design flood discharge and peak hour with Nakayasu Synthetic Unit Hydrograph (HSS) method, GAMA I, HEC-HMS and rainfall discharge model with HEC_RAS 2D in Manikin Dam watershed. In this study, 6-hour rainfall witha return period of 50 years and 100 years was used. Based on the analysis results, the calculation of the hydrological numerical model flood discharge with the HEC-HMS method with a return period of 50 years and 100 years is 511.90 m³/s and 599.30 m³/s with a peak time at the 4th hour. The peak discharge valuesobtained using the Nakayasu Synthetic Unit Hydrograph and GAMA I methods with a return period of 50 years and 100 years are 342.11 m³/s, 381.14 m³/s and 406.44 m³/s, 456.13 m³/s, and the peak time obtained at SUH Nakayasu is 3 hours and GAMA I is 4 hours. Numerical model results with HEC-RAS 2D v6.6 with 6hours of rainfall on the grid obtained peak discharge Hydrograph values for the 50-year and 100-year return periods of 494.86 m³/s and 604.88 m³/s, with the peak time at the 5th hour. Therefore, the largest peak discharge and peak time results were obtained from the HEC-HMS method among the three SUH formulas and HEC-RAS calculations